Developing Call Based Dichotomous Key and Understanding Playback Call Responses Among Sarawak Frogs - Muhammad Fadzil, Amram (Universiti Malaysia Sarawak (UNIMAS), 2021)
Anurans advertisements calls are very diverse; with each species has its own call. Sound produced by the anurans can be a prezygotic isolating mechanism that ensures the survival of the species, as only the fittest will be chosen by the conspecific female to produce progenies. The objective of this study are 1) To determine unique sound characteristics for species identification, 2) To reconstruct phylogeny based on those unique call characteristics, 3) To validate species status of the anuran being studied using vocalisation by doing playback recording, and 4) To develop a dichotomous key based on advertisement calls. Described here were the advertisement calls of 47 species of Sarawak frogs, with 10 from the Family Bufonidae, three from Dicroglossidae, seven from Megophryidae, eight from Microhylidae, 11 from Ranidae, and eight from Rhacophoridae, recorded from 15 study sites in Sarawak. The calls of the male Sarawak frogs were successfully analyzed and described using SoundRuler Acoustic Analysis ver 0.9.6.0 and further determine whether the call characteristic can be used to differentiate the species. Through the Principal Component Analysis (PCA), Discriminant Function Analysis (DFA) and Multivariate analysis it was discovered that the variations of the advertisement call of Sarawak frogs could be used to discriminate the species. For PCA, a total of 25 variables were meaningful in describing the call characteristics of Sarawak Frogs. As for DFA, the heaviest loaded variables in all three functions are from pulse group. Call note, pulse duration, call energy, call frequency and call intensity are the useful groups in discriminating the frog species. Cluster analysis method partially successful in clustering the frog species based on their advertisement call characteristic, especially the frequency group. Through phylogenetic analysis on the calls, constructed neighbor-joining (NJ) and maximum parsimony (MP) tree produced different topology. Both trees show weak support, with most of the nodes have low bootstrap values. For calls validation, the responses of both male and female frogs from three species were observed by playing the advertisement call of the species at their breeding site. Male of all three species responded to the calls, and almost no reaction from female frogs. Next is developing dichotomous key based on the characters of advertisement calls by using meaningful call characters from PCA and DFA. Dichotomous key based on Sarawak frogs’ call were successfully constructed. The key was successfully tested using Leptolalax gracilis calls. The identification of calling characters that can be used to distinguish frog species are very important as it specifies an alternative approach of classifying anuran species other than morphological and DNA variations. It will useful for quicker species identification, and help in solving the taxonomic status of the frogs, for future management and conservation purposes. Keywords: Anuran, bioacoustics, call characters, dichotomous key, Sarawak frogs